From start-up to scale-up: examining public policies for the financing of high-growth ventures - Gilles Duruflé; Thomas Hellmann; Karen E. Wilson (Bruegel, 2017)
We examine the challenge entrepreneurial companies face in going beyond the start-up phase and growing into large successful companies. We examine the long-term financing of these so-called scale-up companies, focusing on the United States, Europe and Canada. We first provide a conceptual framework for understanding the challenges of financing scale-ups. We then show some data about the various aspects of financing scale-ups in the US, Europe and Canada. Finally we raise the question of long-term public policies to support the creation of a better scale-up environment.
Keywords: 330